2012
DOI: 10.1007/s10714-012-1342-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening of cosmological constant for de Sitter Universe in non-local gravity, phantom-divide crossing and finite-time future singularities

Abstract: We investigate de Sitter solutions in non-local gravity as well as in non-local gravity with Lagrange constraint multiplier. We examine a condition to avoid a ghost and discuss a screening scenario for a cosmological constant in de Sitter solutions. Furthermore, we explicitly demonstrate that three types of the finite-time future singularities can occur in non-local gravity and explore their properties. In addition, we evaluate the effective equation of state for the universe and show that the late-time accele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 135 publications
(102 reference statements)
1
71
0
Order By: Relevance
“…25 For a study of the type of future singularities caused by phantom dark energy see [34] and for the case where this occurs with the Deser-Woodard type of non-locality see [30]. case here, but we can still find the explicit solution for a(t) in the far future by proceeding perturbatively.…”
Section: Future Singularitymentioning
confidence: 88%
See 1 more Smart Citation
“…25 For a study of the type of future singularities caused by phantom dark energy see [34] and for the case where this occurs with the Deser-Woodard type of non-locality see [30]. case here, but we can still find the explicit solution for a(t) in the far future by proceeding perturbatively.…”
Section: Future Singularitymentioning
confidence: 88%
“…This fact has actually been one of the main theoretical justifications for studying non-local actions [6,13,44]. The problem with this interpretation however is that the nonlocal corrections one would expect from gravitational/matter loops look nothing like (1.1) 30 . Recently, in [33] the authors have actually shown that a large class of phenomenological models, including (1.1), fails indeed to capture even qualitatively the non-local effects that are expected from quantum corrections on cosmological backgrounds.…”
Section: A Relation To Quantum Theory?mentioning
confidence: 99%
“…Such a theory can be regarded as modified gravity because the R 2 term or its higher derivative term of the trace-anomaly term R, which leads to the long enough inflation and graceful exit from it [21], is the effective action of gravity, where is the covariant d'Alembertian for a scalar quantity. (In References [23][24][25], the features of inflation in non-local gravity including such a non-local term as R has been analyzed in detail.) In this paper, we review the main results in References [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Its theoretical structure and cosmological consequences for different choices of the function f (✷ −1 R) have been discussed in a number of papers, see e.g. [77][78][79][80][81][82][83][84][85][86][87]. In this approach there is no basic principle that fixes the function f (✷ −1 R), which is therefore chosen on purely phenomenological grounds, and can be reconstructed so to fit any given expansion history [88,89].…”
Section: Introductionmentioning
confidence: 99%